The plight of single-parent families.[article]. - Johnson, Norine
Research findings from abroad regarding the effects of the father-absent family on the child and on the mother were reviewed. While both negative and positive effects were pointed out, it was also stressed that the role that the father played in the child's development and in the family structure would first have to be understood before a proper evaluation of the effect that his absence would have could be made. An attempt was made to relate such findings to the Philippine situation wherein more and more fathers and husbands are leaving for the Middle East, thus leaving behind them a growing number of single-parent families. Factors which may help in reducing the effect of the father's absence were identified, and suggestions were made regarding how psychologists and health providers could take a more active role in weaving these factors into more concrete programs to help those who are left behind. -- (from the author)